Ecological population dynamics, host preferences, and associated parasitoids of Bactrocera carambolae and Bactrocera papayae on fruits - D. Koswanudin; H. Widyanto; D. Hutapea; Wawan ,; R. Yuniawati; V.N.O. Subagyo; S. Utami; I.M. Samudra; W. Darwiati (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Fruit flies are a significant pest affecting fruit production in Indonesia. Understanding the species of fruit flies in fruit-growing regions is crucial for evaluating pest risk, establishing effective plant quarantine measures, and managing control programs. The study objectives were conducted to analyze the population dynamics and host preferences of Bactrocera carambolae and Bactrocera papayae on several fruit plants and to study parasitoids associated with the two fruit fly species.METHODS: The study was conducted using a survey method in Bogor, Depok, and Indramayu Regency fruit gardens by installing methyl eugenol traps. The infected fruits were collected randomly and transferred to the laboratory in cages until the fruit flies emerged.FINDINGS: The results show that Bactrocera carambolae was more abundant than Bactrocera papayae captured in methyl eugenol-baited traps, particularly during the rainy season. Bactrocera carambolae favored star fruit as a host (907.79 flies/trap/month), while Bactrocera papaya preferred papaya (208.46 flies/trap/month), highlighting their distinct oviposition behaviors. The average catches indicated that Bactrocera carambolae thrived in moist conditions, while Bactrocera papayae flourished in warmer temperatures. Four parasitoid species were identified, including Diachasmimorpha longicaudata and Fopius arisanus, with parasitization rates of 20.40 percent and 12.70 percent, respectively. These results highlight their potential for effective biological control of the target pest species. The findings suggest that seasonal fluctuations in host fruit availability and climate significantly impact fruit fly populations and their interactions with parasitoids.  CONCLUSION: This study emphasizes the population dynamics and host plant preferences of Bactrocera carambolae and Bactrocera papayae in West Java, Indonesia. Four parasitoid species were identified, with Diachasmimorpha longicaudata and Fopius arisanus showing high parasitism rates, suggesting their potential to control fruit fly populations. The study highlights the importance of climate and host availability in developing sustainable and effective pest management strategies for the fruit industries in Indonesia.